A CLINICAL STUDY ON HIV/AIDS WITH SPECIAL REFERENCE TO ITS PULMONARY MANIFESTATIONS IN A TERTIARY CARE HOSPITAL OF NORTH-EAST INDIA - Dr. Kalyan Kumar Nath; Dr. Rupam Pegu; Dr. Neena Nath; Dr. Diganta Buragohain; Dr. Swaroop Kumar Baruah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ObjectiveTo study the clinical presentation, pattern of opportunistic infections and the pattern of pulmonary disease in HIV/AIDS patients in a tertiary care Hospital of north-east India.MethodsThis is a hospital-based observational study among 205 selected adult patients with HIV/AIDS(as per NACO guidelines) attending the Gauhati Medical College Hospital from1st July, 2018 to 30th June, 2019. A detailed clinical history of the selected cases were recorded in standard Performa including demographic profile, transmission dynamics and clinical profile including CD4 count.ResultsThe age of the study population ranged from 15 to 68 years. The maximum number of patients were in the age group of 21 to 30 years (68 cases, 33.17%). Majority of the patients were male (61.46%). Majority of the patients were married (67.80%)and literate (94.15%). The most common affected group was housewives (26.81%) followed by security personnel (14.51%), businessmen (12.68%), students (11.71%), and drivers (4.49%). The most common route of transmission was heterosexual (77.56%), followed by MSM (12.19%), intravenous drug users (2.44%) and unknown route (3.41%). Fever was the most common presenting symptom (40.49%), followed by diarrhoea (30.24%), weight loss (29.76%), cough (16.10%), pain abdomen (5.76%), skin problem (6.83%), dysphagia(4.88%), dyspnoea (3.5%), oral ulcers(4.88%), neck swelling (3.90%), palpitation(3.90%), chest pain (2.65%), hemoptysis (2.93%), malaise(2.93%), anorexia (2.93%) and genital ulcer (2.44%).Opportunistic infection was found in 112 patients (54.63%). Tuberculosis was the commonest OI, being diagnosed in 44 patients  (39.29%), followed by Candidiasis (28 cases, 24.78%), Chronic diarrhoea (26 cases, 23%),  bacterial pneumonia (13 cases, 11.5%), Herpes zoster (8 cases, 7.07%), Pneumocystic carinii pneumonia (3 cases, 2.65%), Cryptococcal Pneumonia (3 cases, 2.65%), Penicillium marneffi infection  (2 cases, 1.65%) and Molluscum contagiosum (1case, 0.89%).The median CD4 count in patients with OI was 194/cumm and those without OI was 638/cumm, which is statistically significant with P value of 0.0185. Pulmonary manifestations were present in 20.98% cases. Out of all pulmonary manifestations, Pulmonary Tuberculosis (60.47%) was the commonest, followed by bacterial pneumonia (30.23%), PCP (6.98%) and ILD(2.33%).ConclusionsIn the present study, HIV was mainly observed in the economically productive young males and females. Housewives were the most affected group followed by service holders (security personnel) with heterosexual transmission being the most common route. Fever was the most common presenting symptom followed by diarrhoea, weight loss, cough. Tuberculosis was the most common opportunistic infection followed by candidiasis, chronic diarrhoea and respiratory tract infection. There is a statistically significant inverse relationship between opportunistic infection and CD4 count. Similarly, Extra-Pulmonary Tuberculosis was more with low CD4 count compared to Pulmonary Tuberculosis, which is statistically significant. Pulmonary tuberculosis was the most common pulmonary manifestation followed by lower respiratory tract infection, PCP pneumonia and interstitial lung disease.